The Application of Far-Infrared in the Treatment of Wound Healing - Yu-Hsin Lin PhD; Tzong-Shiun Li MD, PhD (Journal of Evidence-Based Complementary & Alternative Medicine, 2017)
Far-infrared (FIR) radiation therapy has been used for soothing effect in wound treatment. Studies have shown that FIR could enhance wound healing processes in rat models. Although these research results supported that FIR may play an important for wound healing, it had no consensus in clinical practices. It is suggested that more persuasive systemic clinical researches are needed to explore the effectiveness of FIR therapy for wound healing.